Overcoming (hyper)modernity - Gilmozzi, Giacomo (B@belonline, 2024)
Sketching the contours of a possible posthumanist alliance – integrating insights from poststructuralism, critical posthumanism, new materialism and the anthropological turn compatible with the organological-pharmacological framework proposed by Bernard Stiegler – this article aims to contrast modern dualisms and their instrumental conception of nature (as a resource) and technology (as a tool) which are symptomatically embodied today by the solutionist, anthropo- and technocentric approach of transhumanists. It is here argued that posthumanism, as outlined by Francesca Ferrando, offers a viable path for overcoming hypermodernity (Bernard Stiegler) towards a normative – rather than descriptive – conception of postmodernity thanks to a coherent conceptual ensemble that is both epistemologically and politically needed for bifurcating from the present crisis. This drastic shift requires, on the one hand, a theoretical rethinking of the relations between the “human” (understood in its indivisibility and its co-evolutionary relations with the technological, social and ecological systems in which it lives) and the more-than-human; and, on the other hand, the imagination of practical ways for implementing the ecological and the technological transitions, emphasizing the importance of developing politics of technologies that promotes the search for trans-local ecological (in the triple meaning given by Felix Guattari) therapies.